Cadmium in the roots and leaves of tea (Camellia sinensis L.) at PTPN 7 Pagar Alam unit, South Sumatra, Indonesia - Siti Tri Pebriani Daulay; Dedik Budianta (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
The excessive and intensive application of chemical fertilizers can increase the concentration of heavy metals in the soil. This study aimed to determine Cd deposition in tea roots and leaves using the Detailed Survey method, with sampling points determined using the stratified sampling method, which involves dividing the samples into several age ranges for the plants. The average concentration of Cd in the roots was 0.015 ± 0.004 mg/kg, while in the tea leaves it was 0.010 ± 0.003 mg/kg. The absorption of Cd in tea plant leaves shows the lowest average absorption rate in samples aged 15–25 years, particularly in plants that were 1 year old after production pruning, at 0.005 mg per plant. However, its content remains well below the maximum threshold of cadmium in tea, which was set at 1.0 mg/kg. The age of the plants does not substantially affect the accumulation of Cd in tea leaves; however, tea pruning does affect the accumulation of Cd in the leaves. The research findings indicate that the concentration of Cd in the roots and leaves of tea plants was very low, far below the established Cd threshold, influenced by regular pruning, which results in minimal Cd absorption in the tea leaves. Leaves were considered safe for consumption by humans and animals. Data on the levels of Cd in tea roots and leaves are still rarely found, so it was recommended to further investigate Cd in tea roots and leaves.